PENGARUH TINGKAT INFLASI, SUKU BUNGA DAN NILAI TUKAR TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG LISTING DI BURSA EFEK INDONESIA PERIODE TAHUN 2008 - 2012 - Santoso, Cahyo Budi (Universitas Riau Kepulauan, 2015)
Linda Rosalina, NPM 11.10.0.069 â€œInfluence of Inflation, Interest Rate, and Exchange Rate of Banking Financial Companies Listed on the Indonesia Stock Exchange (IDX)Â year periode in 2008-2012â€. Supervisor I by Jayana Salesti, SE, CA, MM and Supervisor II by Bosar Hasibuan, SE, M.Ak.The Purpose of the research to find out Influence of Inflation, Interest Rate and Exchange Rate. Performance of Banking Financial Companies Listed on the Indonesia Stock Exchange. the Research Conducted based on financial ratio 5 years periode in 2008 until 2012, where Bank during Performance Benchmark is ROA, ROE, NIM.In The research, the researcher use multiple linear regression methode to establish the dependent Variabel is Return on Asset (ROA), Return on Equity (ROE), Net Interest Margin (NIM) and Dependen Variabel is Inflation, Interest rate, and Exchange rate. Before Analiyzing the result of regression, the first result and their Signifikansi tested classical assumption, so it can be ascertained that the result meet the standard of the BLUE.The Result of the research that inflation, interest rate and exchange rate can be influence significant of ROA, ROE, NIM. however the result must still be assessed by observation methode better, in the next time.Keywords : Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), Inflation, Interest Rate and Exchange Rate.